I Wore This Dress Today for You, Mom - Dower, Kim (Book collections on Project MUSE., 2022)
"Kim Dower's poetry has been described by the Los Angeles Times as "sensual and evocative . . . seamlessly combining humor and heartache," and by O Magazine as "unexpected and sublime." Acclaimed for combining the accessible and profound, her poems about motherhood are some of her most moving and disarmingly candid. I Wore This Dress Today for You, Mom is an anthology of her poems on being a mother-childbirth to empty nest-as well as being a daughter with all the teenaged messiness, drama and conflict, to finally caring for one's mother suffering from dementia. Culled from her four collections as well as a selection of new work, these poems, heartbreaking, funny, surprising, and touching, explore the quirky, unexpected observations, and bittersweet moments mothers and daughters share. These evocative poems do not glorify mothers, but rather look under the hood of motherhood and explore the deep crevices and emotions of these impenetrable relationships: the love, despair, joy, humor and gratitude that fills our lives"--